The Application of Fuzzy-Analytical Hierarchy Process Method for Majors Selection at Public Universities - Addin Aditya; Febry Eka Purwiantono (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2020)
The purpose of this research is to build a decision support model for prospective students in choosing undergraduate programs at state universities after they accomplished their high school. There are more than 800 undergraduate programs from science and technology departments from 40 state universities in Indonesia. In this research, we use the Fuzzy Analytical Hierarchy Process (F-AHP) to model a decision. This method is chosen because able to make comparisons between criteria more complex than other DSS (Decision Support System) methods. For the criteria used in this research is computer-based test result, student capacity in 2019 and the people who interest in those majors in 2018. The main result of this research is a ranking of science and technology departments at 40 state universities in Indonesia. The results of this research are expected to be able to assist students in choosing majors that will be taken after graduation in their school. In addition, the method of this research can also be continued in subsequent researches that are similar (theoretically). Whereas practically, this method can be implemented every year using different data.